The Influence of Entrepreneurship and Career Planning in the Regeneration of Dentist Family Businesses in Indonesia - Stanley Santosa Kamadjaja; Metta Padmalia (Denta Journal Kedokteran Gigi, 2025)
Background: Many children of parents working in the healthcare industry tend to pursue the same profession as their parents or family members. Dentistry is one of the medical professions often passed down to the next generation, as children grow up observing their parents, close relatives, or role models. This study explores the role of Entrepreneurship and Self Efficacy in influencing career selection among second or later-generation dentists. Career selection motivation is shaped by both internal and external factors, including the entrepreneurial drive to manage and sustain a family-owned dental practice. Objective: This research aims to provide insights into the motivations underlying career choices in dentistry. Materials and Methods: A purposive snowball sampling technique was used to collect data from 50 dentists across various cities in Java, Indonesia, all of whom are at least second-generation dentists actively working in family-owned or independent practices. Results: The findings highlight that motivation and Career-Related Modeling play a significant role in shaping the career preferences of second-generation dentists, particularly in family-owned businesses. This study contributes to understanding how entrepreneurial influences and career role models impact career decisions in the field of dentistry. Conclusion: The results of this research highlighted the dominant influence of entrepreneurial drive in second and later generation dentist in choosing dentist as a profession.